Early caregiving predicts attachment representations in adolescence: findings from two longitudinal studies. (14th June 2018) - O'Connor, Thomas G.; Woolgar, Matthew; Humayun, Sajid; Briskman, Jacqueline A.; Scott, Stephen
Abstract : Background: A growing research base demonstrates that adolescents' construction of secure attachment relationships may underlie successful social and personal relationships and healthy behavioral adjustment. Little is known about the early caregiving origins of adolescent attachment security; this study provides some of the first data on this topic. Method: The relative contribution of early and current caregiving quality to attachment security in adolescence was assessed in two longitudinal studies of a clinic‐referred and an at‐risk community sample using identical measures ( n  = 209). Quality of early parent–child relationships at age 3–7 years of age and parent–adolescent relationship quality at approximately 12 years were assessed using observational methods; psychosocial risk was derived from extensive interview and questionnaire assessments; adolescent attachment quality was assessed using a standard attachment interview. Results: Analyses indicated moderate stability in observed parent–child interaction quality from early childhood to adolescence. Observational ratings of both early childhood and current caregiving quality were significantly associated with adolescent attachment security; however, early caregiver sensitivity was more strongly associated with adolescent attachment security and predicted later attachment security independently from current caregiving quality. Follow‐up analyses indicated that this longitudinal prediction was significantly weaker in the clinic than in the at‐risk community sample. Conclusions: Parental sensitive responding in childhood has enduring effects on attachment representation in adolescence, independent of current parenting relationship quality. These findings provide important new evidence supporting early parenting interventions for promoting youth well‐being and adjustment.